PENINGKATAN KINERJA KARYAWAN DENGAN PEMBERIAN MOTIVASI DI ORANJE PERGOLA RESTAURANT PADA LIDO LAKES RESORT AND CONFERENCE. - Andi Mardani, - (2009)
This Skripsi aim to know condition of motivation required for employee by seeing that concordance from form motivation that given by organizer and then can obtain an exploitation plan of human resource in Lido Lakes Resort And Conference especially Oranje Pergola Restaurant so that becomes input which good for organizer in the effort increasing performance employee. Oranje Pergola Restaurant is a restaurant which could accommodate 150 indoor client and terrace and accommodate catering services front of gate into Lido Resort which Lake, Mt. Pangrango and sunrise view at the morning. The research method applied is descriptive-kualitatif , and collecting data by quosioner, interview, and documentation study. Excitement of Employee motivation is studied by seeing perception of requirement would motivation excitement required by employee in they work activity now, and sees also perception of supervisor in perception a motivation excitement express form of motivation applied to all employee. The happening of difference of perception between form of motivations given by supervisor to employee with requirement employee itself will cause behavior and changing value tends to towards negative because job satisfaction which has not fulfilled Based on research result, known that condition from motivation excitement of employee has fulfilled enough, but From this research there is known that there is some lack of hygiene factor and motivator factor to increase job performance, that shows still need improvement. Based on that result, the suggestions for management recommends an exploitation of human resource which can uplift skill or ability and develops job motivation of employee.